The Amyand's Hernia: A Rare Clinical Entity Diagnosed by Computed Tomography. (11th April 2013) - Keskin, Suat; Şimşek, Cihan; Keskin, Zeynep
Abstract : Amyand's hernia, named for the first person to describe an inguinal hernia containing the vermiform appendix, is an uncommon variant of an inguinal hernia. Amyand's hernia is an extremely rare condition and is often misdiagnosed. Traditionally, these hernias have been diagnosed at surgery but are increasingly diagnosed by abdominal computed tomography (CT) scans. CT of the abdomen may help in guiding the diagnosis.